Study of the effect of cyclophosphamide and doxorubicin on the progress of pregnancy and histomorphological structure of the ovaries of white rats - Heybatova, M. F. (Journal of Neonatal Surgery, 2025)
The article is devoted to the study of changes in the course of pregnancy and final outcomes against the background of the introduction of cyclophosphamide and doxorubicin to pregnant female white rats, as well as morphohistological changes developing in organs against the background of the introduction of cyclophosphamide and doxorubicin. The results of the studies showed that the duration of pregnancy in pregnant females receiving cyclophosphamide at a dose of 10 mg / kg decreased by 27.1% compared with the control group, the prenatal weight of animals decreased by 39.3% compared with the control group, and the postnatal weight decreased by 33.4%. The difference between prenatal and postnatal weight was 56.8%. The number of cubs decreased by 40.6%, and their weight by 43.9% compared with the number of cubs in the control group. When cyclophosphamide was prescribed at a dose of 20 mg / kg, the changes that occurred in the mother and offspring during pregnancy were more serious. In pregnant rats given doxorubicin at a dose of 2.5 mg/kg twice a week from the 8th day of pregnancy, the duration of pregnancy was 18.5% shorter compared to females in the control group, the prenatal weight of the animals decreased by 28.2% compared to the control group, and the postnatal weight by 29.9%. The difference between prenatal weight and postnatal weight was 25.4%. The number of pups also decreased by 29.8% compared to the number of pups in the control group. The birth weight of pups also decreased by 27.3% compared to the control group. These parameters decreased more significantly with the introduction of doxorubicin at a dose of 5 mg/kg. In pregnant rats given cyclophosphamide at a dose of 10 mg/kg and doxorubicin at a dose of 2.5 mg/kg from the 8th day of pregnancy for 1 week, the duration of pregnancy was reduced by 50.5%. The prenatal weight of the animals decreased by 50.2% compared to the control group, and the postnatal weight by 47.7%. The difference in prenatal and postnatal weight was 57.6%. A decrease in the number of pups by 90.1% was noted. The weight of the pups at birth also decreased by 50.7%. Against the background of the combined administration of cyclophosphamide at a dose of 20 mg/kg and doxorubicin at a dose of 5 mg/kg, the pregnancy did not end normally, and since the birth of cubs was not observed, the number of cubs was not determined, and since cubs were not born, it was not possible to determine their weight. When studying the histomorphological changes developing in the ovaries against the background of the administration of cytostatics to female rats for a week, it was shown that destructive changes, leukocyte infiltration and cellular edema are observed in the organs